Bathing water profile in the coastal belt of the province of Pescara (Italy, Central Adriatic Sea). Issue 1 (15th June 2015) - Liberatore, Lolita; Murmura, Federica; Scarano, Antonio
Highlights: The quality of bathing water is fundamental for environment and tourism. This paper examines the water profile in the coastal belt of the province of Pescara. The reference is Directive 2006/07 of European Commission. The data highlight critical situations in various parts of the coast. These problems can be attributed the river pollution. Abstract: The quality of bathing water is fundamental, not only from an environmental point of view but also due to the economic importance of tourism. This paper examines the water profile in the coastal belt of the province of Pescara (Italy, Central Adriatic Sea) with reference to the microbiological parameters Escherichia coli and intestinal enterococci required by Directive 2006/07 of European Commission. The water quality of 15 coastal beaches was surveyed; data were produced from monitoring and controls made available by the Abruzzo Regional Environmental Prevention and Protection Agency (ARTA) and extracted and elaborated for the period of interest (2010–2013). Statistical analysis was used to confirm the aspects deduced from mean values of monitoring and control data for each stretch. The data highlight critical situations in various parts of the coast; these problems can be attributed to river pollution, mainly due to the malfunctioning of the treatment plants for urban wastewater.